Development of statistical process control (SPC) matlab-based software for automotive industries application - Siti Hazlina, Mokhtar (2012)
This project is motivated by an interest in promoting the use computer-based statistical process control (SPC) in manufacturing sector specifically for automotive industries in Malaysia. The use of computer-based SPC is essential in quality function. They are capable to perform various operations or tasks very accurately at fast speeds. SPC techniques are simple statistical techniques to help identify process problems and it can be implemented as simple as analyzing data and plotting charts. However, the development of SPC in Malaysian small and medium-sized enterprises (SMEs) is found lacking because they remain to use traditional SPC techniques which the data are calculated and analyzed manually. Consequently, manual work on traditional SPC has focused on particular limitations; with only little quality faults are detectable, time-consuming and burdensome. This paper highlights the results of an effort to design the SPC computer-based system for conducting simple statistical analysis. The system named as MagNa version 1.0 MATLAB-based software, which is able to offer more benefits to the Malaysian SMEs specifically for automotive industries application.